Nanopolymers Delivery of the Bone Morphogenetic Protein-4 Plasmid to Mesenchymal Stem Cells Promotes Articular Cartilage Repair In Vitro and In Vivo. (11th April 2012) - Shi, Junjun; Zhang, Xin; Pi, Yanbin; Zhu, Jingxian; Zhou, Chunyan; Ao, Yingfang
Abstract : The clinical application of viral vectors for gene therapy is limited for biosafety consideration. In this study, to promote articular cartilage repair, poly (lactic-co glycolic acid) (PLGA) nanopolymers were used as non-viral vectors to transfect rabbit mesenchymal stem cells (MSCs) with the pDC316-BMP4-EGFP plasmid. The cytotoxicity and transfection efficiency in vitro were acceptable measuring by CCK-8 and flow cytometry. After transfection, Chondrogenic markers (mRNA of Col2a1, Sox9, Bmp4, and Agg) of experimental cells (MSCs being transfected with BMP-4 plasmid by PLGA nanopolymers) were increased more than those of control cells (MSCs being transfected with naked BMP-4 plasmid alone). In vivo study, twelve rabbits (24 knees) with large full thickness articular cartilage defects were randomly divided into the experimental group (MSCs being transfected with BMP-4 plasmid by PLGA nanopolymers) and the control group (MSCs being transfected with naked BMP-4 plasmid). The experimental group showed better regeneration than the control group 6 and 12 weeks postoperatively. Hyaline-like cartilage formed at week 12 in the experimental group, indicating the local delivery of BMP-4 plasmid to MSCs by PLGA nanopolymers improved articular cartilage repair significantly. PLGA nanopolymers could be a promising and effective non-viral vector for gene therapy in cartilage repair.